The linkages of plant, litter and soil C:N:P stoichiometry and nutrient stock in different secondary mixed forest types in the Qinling Mountains, China - Pang, Yue; Tian, Jing; Zhao, Xuan; Chao, Zhi; Wang, Yuchao; Zhang, Xinping; Wang, Dexiang (PeerJ (San Francisco, CA), 2020)
Carbon (C), nitrogen (N) and phosphorus (P) stoichiometric ratios are important indicators of ecosystem function and productivity. However, few studies have assessed the nutrient relationship between plant, litter and soil, and the nutrient stock in different secondary mixed forest types. We investigated the C, N and P concentrations and stoichiometric ratios in trees, understory plants, litter and soil layers in three different secondary mixed forest types (broadleaf mixed forests (BM), broadleaf-conifer mixed forests (BCM) and coniferous mixed forests (CM)) in the Qinling Mountains. The results showed that significant differences in C:N:P stoichiometry were detected in multiple organs in the vegetation layers in the different forest types. Trees, shrubs and herbs all allocated more N and P in leaves and had a higher N:P ratio in leaves than in other organs. The C concentrations, C:N ratios and C:P ratios of all tree organs showed a decreasing order: BM < BCM < CM, while the N and P concentrations showed an increasing order: BM > BCM > CM. For litter and soil, BM had generally higher N and P concentrations than those of BCM and CM. The highest N and P stock was in tree branches-not in the stem, which had the highest biomass (except for P in CM). Compared with other forest types, CM stored more nutrients in the labile litter layer, while BM stored more nutrients in the stable soil layer. The net ecosystem nutrient element stock in BM was generally higher than that in BCM and CM. The C, N and P concentrations and stoichiometry in the plant organs, litter and soil were significantly correlated. Our findings demonstrate that nutrient concentrations in plant organs, litter and soil are tightly linked in secondary mixed forests.